An Investigation of the Interest Rate Risk and Exchange Rate Risk of rhe European Financial Sector: Euro Zone Versus Non-Euro Zone Countries - Amalia Di Iorio; Robert Faff; Harald Sander (Journal of Accounting and Management Information Systems (JAMIS), 2013)
This paper examines the sensitivity of financial sector stock returns to two risk factors – interest rates (both long-term and short-term) and exchange rates. Specifically we investigate the impact of the European Union and the introduction of the euro on European financial sector risk in the framework of a comparative analysis of financial sector returns across three broad groupings (Banking, Financial Services and Insurance) for a representative group of key euro and non-eurozone countries. Further we investigate the nature of interest rate and exchange rate exposure across increasing time horizons, enabling us to examine both its short and long-term effects on stock returns. Generally, our findings suggest that while Banks are more sensitive to short-term interest rates, the Financial Services and Insurance sectors are more sensitive to long-term interest rates. There is no notable trend in sensitivity pre-/post-euro and differences in terms of the impact of interest rate changes across countries seem to suggest (i) some evidence of integration, and (ii) differences in financial structures and regulation. Further, interest rate sensitivity increases significantly with increasing time intervals. Evidence of exchange rate exposure is weak across all countries and sectors although there is some evidence that it increases with increasing time intervals. Differences in sensitivity can be related to differences in international activities.
Keywords: F31; G21; G22; G23; E43; 650; Interest Rate Risk; Exchange Rate Risk; European Financial Sector; Intervaling